The Relationship Between Precocious Puberty and Premature Thelarche with Serum Irisin Levels - Özgen, İlker Tolga; KUTLU, ESRA; Kutlu, Esra; ÖZGEN, İLKER TOLGA; BULUT, HURI; Bulut, Huri; Temur, Hafize Otcu; TORUN, EMEL; Torun, Emel; CESUR, YAŞAR; Cesur, Yaşar (My University, 2019)
https://www.karger.com/?DOI=10.1159/000495021